Radiatively efficient accreting black holes in the hard state: the case study of H1743–322 - Coriat, M.; Corbel, S.; Prat, L.; Miller-Jones, James; Cseh, D.; Tzioumis, A.; Brocksopp, C.; Rodriguez, J.; Fender, R.; Sivakoff, G. (Wiley-Blackwell Publishing Ltd., 2011)
In recent years, much effort has been devoted to unravelling the connection between the accretion flow and the jets in accreting compact objects. In the present work, we report new constraints on these issues, through the long-term study of the radio and X-ray behaviour of the black hole candidate H1743-322. This source is known to be one of the ‘outliers’ of the universal radio/X-ray correlation, i.e. a group of accreting stellar-mass black holes displaying fainter radio emission for a given X-ray luminosity than expected from the correlation. Our study shows that the radio and X-ray emission of H1743-322 are strongly correlated at high luminosity in the hard spectral state. However, this correlation is unusually steep for a black hole X-ray binary: b~ 1.4 (with Lradio?LbX). Below a critical luminosity, the correlation becomes shallower until it rejoins the standard correlation with b~ 0.6. Based on these results, we first show that the steep correlation can be explained if the inner accretion flow is radiatively efficient during the hard state, in contrast to what is usually assumed for black hole X-ray binaries in this spectral state. The transition between the steep and the standard correlation would therefore reflect a change from a radiatively efficient to a radiatively inefficient accretion flow. Finally, we investigate the possibility that the discrepancy between ‘outliers’ and ‘standard’ black holes arises from the outflow properties rather than from the accretion flow.